The fox and the stork - Parker, Victoria (Thaxted, Miles Kelly, 2013)
The text is young and simple, and clearly portrays helpful morals through fun characters that young readers can relate to. All of the classic, best-loved fables have been included, as well as some lesser-known stories that have been retold to intrigue and entertain children for the very first time
Keywords: English